Quali concimi, per quali suoli? Alberto De Dominicis e i concimi azotati nel Mezzogiorno d’Italia fra le due guerre mondiali. - Andreoni, Luca (OS. Opificio della Storia, 2022)
The purpose of this article is to reconstruct a piece of the debate on the paths to the modernization of agriculture in the Southern Italy between the two world wars, through the position of one of the protagonists of the time, Alberto De Dominicis (1879-1952). What drives this research is the intent to investigate the composite matrix of the intense debate, which accompanied the progressive and uneven spread of chemical fertilizers, specifically, nitrogen fertilizers. After an introductory paragraph, the agronomic aspects and the roots of this debate in Italy and outside Italy are reconstructed in the second paragraph. Paragraph 3 is dedicated to the agronomic issues of De Dominicis’ thought, while paragraph 4 deals with the relationship between economy, environment and education in the complex issue of the adoption of chemical fertilization, object of the reflection of De Dominicis. Conclusions follow (paragraph 5).